2014
DOI: 10.1590/0037-8682-0262-2013
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic interactions in mixed-species biofilms of pathogenic bacteria from the respiratory tract

Abstract: Introduction: Mixed-species biofi lms are involved in a wide variety of infections. We studied the synergistic interactions during dual-species biofi lm formation among isolates of Pseudomonas aeruginosa, Acinetobacter baumannii, and Stenotrophomonas maltophilia. Methods: Isolates were cultured as single-species and all possible combinations of dual-species biofi lms. Results: The 61 A. baumannii biofi lms increased by 26-fold when cultured with S. maltophilia isolates; 62 A. baumannii biofi lms increased by 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 14 publications
2
14
1
Order By: Relevance
“…lac operon 47 . Further, the coexistence of Gram-positive and Gram-negative bacteria in multispecies or polymicrobial biofilms at oral or dental plaque 48 , 49 , respiratory tract 50 , catheters 51 , surface of marine algae 52 and many more further strengthen our findings. Although the instances for the occurrence of LuxR is very high as compared to LuxI that explain the extent for responding to QSSMs are very high as compared to synthesis in Gram-positive bacteria.…”
Section: Discussionsupporting
confidence: 76%
“…lac operon 47 . Further, the coexistence of Gram-positive and Gram-negative bacteria in multispecies or polymicrobial biofilms at oral or dental plaque 48 , 49 , respiratory tract 50 , catheters 51 , surface of marine algae 52 and many more further strengthen our findings. Although the instances for the occurrence of LuxR is very high as compared to LuxI that explain the extent for responding to QSSMs are very high as compared to synthesis in Gram-positive bacteria.…”
Section: Discussionsupporting
confidence: 76%
“…It was found that S. maltophilia increases the risk of resistance of P. aeruginosa to polymyxin; beta-lactamase leaking from S. maltophilia enhances the growth of P. aeruginosa in the presence of beta-lactam antibiotic agents; S. maltophilia might confer a selective fitness advantage to P. aeruginosa and increase the virulence of P. aeruginosa (18). The interaction of A. baumannii and S. maltophilia is not discussed in the literature, except for their ability to increase each other's biofilm production (19). It was reported that a Burkholderia cenocepacia subpopulation highly resistant to polymyxin B can protect a sensitive P. aeruginosa from polymyxin B in broth co-culture (20).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, it evaluates the nature of interactions occurring between P. aeruginosa and S. maltophilia under both planktonic and biofilm growth, and specifically whether these interactions offer enhanced fitness compared to single cultures. Secondly, it considers S. maltophilia and P. aeruginosa strains isolated at the same time from the same CF patient during a PE episode, whereas previous works were conducted using strains isolated from different, and non-CF, patients (Kataoka et al, 2003 ; Ryan et al, 2008 ; Varposhti et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%